Formación de burbujas financieras y crisis: de la crisis del Nasdaq a la crisis de la hipotecas subprime - Vilariño, Ángel (Papeles de Europa, 2009)
Starting from the last two more recent financial bubbles, dot-com companies one, NASDAQ, and the current debt bubble, the article emphasizes the problems in financial risks valuation and measuring and errors in the financial regulatory and supervisory driven by efficient markets paradigm and autoregulation. Based on Turner Review, recently published by the UK Financial Services Authority (FSA), it is established the need for a radical change in the regulatory standards and supervisory practice.
Keywords: Financial risks; Financial regulation; Self-regulation; Internal risk models; Basilea II